Willingness to Pay Masyarakat Terhadap Penggunaan Jasa Pengolahan Sampah - Emalia, Zulfa; Huntari, Dewi (Jurnal Ekonomi Kuantitatif Terapan, 2016)
The aims of this study are to analysis factors such as the amount of income, education level, and the number of frequencies transporting effect on willingness to pay (WTP) by the respondent that using waste management services. This study is to see how much the value of WTP who are willing to pay by the respondents and how much the level of compliance of the respondents in using waste management service in Kelurahan Rajabasa Raya. This study uses data derived from questionnaires. This study uses Binary Logistic Regression with analysis tools SPSS ver. 15.  The results from this study indicate that income and education levels factors have positive and significant effect to WTP. While the frequency of transporting has a positive but not significant effect to WTP. The average value of WTP that willing to pay by respondents is Rp. 18,200. Based on the respondents who are willing to pay and are not willing to pay, we can see the level of compliance of the public against the use of waste management services. By 73 or 77.7% of respondents have a level of compliance with the willing to pay to continue using the waste management services. The remaining 21 respondents, or 22.3% of total respondents have a low compliance.
Keywords: income; education level; frequency of transportation; level compliance; willingness to pay; binary logistic regression